2015
DOI: 10.1177/0003489415582257
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Mutation of NOG Interferes With the Dimerization of NOG and Causes Proximal Symphalangism Syndrome in a Chinese Family

Abstract: Objectives: NOG is an antagonist to bone morphogenetic proteins and plays an important role in proper bone and joint development. Dominant mutations in NOG may lead to a series of symphalangism spectrum disorders. In this study, we aimed to identify the genetic cause and the pathogenic mechanism of an autosomal dominant disorder with cosegregating proximal symphalangism and conductive hearing impairment in a Chinese family. Methods: Mutation screening of NOG was performed in the affected family members by poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…In the family reported here, both cysteine 184 and 230 were affected, resulting in stapes rigidity, hearing loss, and phalangeal dysfunction [16]. These ndings con rm that mutations with the same NOG coding sequence can lead to different phenotypes and inter-family variation [17][18][19][20][21][22][23][24][25] . This suggests that disease expression can be independent of the location and type of NOG mutation.NOG Mutation contains a variety of syndromes.…”
Section: Discussionsupporting
confidence: 73%
“…In the family reported here, both cysteine 184 and 230 were affected, resulting in stapes rigidity, hearing loss, and phalangeal dysfunction [16]. These ndings con rm that mutations with the same NOG coding sequence can lead to different phenotypes and inter-family variation [17][18][19][20][21][22][23][24][25] . This suggests that disease expression can be independent of the location and type of NOG mutation.NOG Mutation contains a variety of syndromes.…”
Section: Discussionsupporting
confidence: 73%
“…In the family reported here, both cysteine 184 and 230 were affected, resulting in stapes rigidity, hearing loss, and phalangeal dysfunction [16]. These ndings con rm that mutations with the same NOG coding sequence can lead to different phenotypes and inter-family variation [17][18][19][20][21][22][23][24][25]. This suggests that disease expression can be independent of the location and type of NOG mutation.…”
Section: Discussionsupporting
confidence: 62%
“…In the family reported here, both cysteine 184 and 230 were affected, resulting in stapes rigidity, hearing loss, and phalangeal dysfunction [24]. These ndings con rm that mutations with the same NOG coding sequence can lead to different phenotypes and inter-family variation [13][14][15][16][17][18]22,25,26]. This suggests that disease expression can be independent of the location and type of NOG mutation.…”
Section: Discussionsupporting
confidence: 62%
“…Nog mutation site and clinical phenotype analysis we searched literature database and PubMED data Library to nd out the relevant literature of nog gene mutation.Tab le 1 lists the nog mutation sites reported so far Clinical phenotype [13][14][15][16][17][18][19]. The results showed that the mutation site of nog was varied, the clinical features also vary.…”
Section: Resultsmentioning
confidence: 99%